112 Is cognition stable in progressive supranuclear palsy after diagnosis, or are we testing the wrong thing?. Issue 3 (9th February 2012) - Ghosh, B; Hodges, J R; Rowe, J B
Abstract : Introduction: Progressive supranuclear palsy (PSP) is an akinetic rigid syndrome, used by Albert in 1974 as a model of subcortical dementia. Despite this, there has been insufficient information regarding progression of cognitive dysfunction during the disease. Methods: We tested 23 patients at baseline and 16 of them after a year interval (four died, three were unable to undergo assessment) with 20 matched controls. Domains tested included executive (Hayling, Brixton, frontal assessment battery, animal and letter fluency); visuospatial (VOSP cube counting); memory (memory section Addenbrookes cognitive examination-revised (ACE-R); mini mental state exam); global function (ACE-R); and the subjective rating of mental function in the PSP rating scale (mPSPRS). Results: Comparison was made between baseline and interval scores in surviving patients. Correcting for multiple comparisons (p<0.005 is significant), none of the objective cognitive measures changed significantly. However, the subjective rating of mental function (mPSPRS), did deteriorate (t= −4.2, df=14, p=0.0005). Conclusions: When corrected for multiple comparisons, none of the objective cognitive tests showed deterioration after a year. This could be due to early deterioration in cognition before diagnosis, with later stabilisation of function. The subjective rating of mental deterioration in the PSPRS did change, although this result may be confounded by apathy or progressive bradyphrenia, rather than loss of cognitive functions per se.